2022
DOI: 10.46497/archrheumatol.2022.9552
|View full text |Cite
|
Sign up to set email alerts
|

Does remission in rheumatoid arthritis bring kinesiophobia, quality of life, fatigue, and physical activity closer to normal?

Abstract: Objectives: This study aimed to compare kinesiophobia, fatigue, physical activity, and quality of life (QoL) between the patients with rheumatoid arthritis (RA) in remission and a healthy population. Patients and methods: The prospective controlled study included 45 female patients (mean age: 54.22±8.2 year; range, 37 to 67 year) with a diagnosis of RA determined to be in remission according to the Disease Activity Score in 28 Joints (DAS28) being ≤2.6 between January 2022 and February 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Mean pain intensity at rest was reported in 45 out of the 74 articles included in the systematic review. Most studies used the Visual Analog Scale 174 (VAS; n = 21) 65,6971,76,78,82,85,89,90,112,114,117,119,120,122,124,126,138,139,141 or the Numeric Rating Scale 175 (NRS; n = 15) 29,62,66,68,75,79,80,83,88,111,113,116,127,128,137 . Other studies used the Knee Injury Osteoarthritis Outcome Score pain subscale 176 (KOOS-P; n = 3) 63,84,134 , Brief Pain Inventory 177 (n = 1) 64 , Oxford Knee Score 178 (OKS; n = 1) 140 , the Quality of Well-Being Scale – Self-administered Pain Scale 179 (QWBS-P; n = 1) 150 , the Short Form 36 bodily pain 180 (SF-36; n = 1) 130 , the Graphic Rating Scale 181 (GRS; n = 1) 133 , Fibromyalgia Impact Questionnaire-Pain 182 (FIQ-Pain, n = 1) 67 and the Verbal Rating Scale 183 (VRS; n = 1) 104 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mean pain intensity at rest was reported in 45 out of the 74 articles included in the systematic review. Most studies used the Visual Analog Scale 174 (VAS; n = 21) 65,6971,76,78,82,85,89,90,112,114,117,119,120,122,124,126,138,139,141 or the Numeric Rating Scale 175 (NRS; n = 15) 29,62,66,68,75,79,80,83,88,111,113,116,127,128,137 . Other studies used the Knee Injury Osteoarthritis Outcome Score pain subscale 176 (KOOS-P; n = 3) 63,84,134 , Brief Pain Inventory 177 (n = 1) 64 , Oxford Knee Score 178 (OKS; n = 1) 140 , the Quality of Well-Being Scale – Self-administered Pain Scale 179 (QWBS-P; n = 1) 150 , the Short Form 36 bodily pain 180 (SF-36; n = 1) 130 , the Graphic Rating Scale 181 (GRS; n = 1) 133 , Fibromyalgia Impact Questionnaire-Pain 182 (FIQ-Pain, n = 1) 67 and the Verbal Rating Scale 183 (VRS; n = 1) 104 .…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-one studies assessed physical activity using a self-reported measure (Table 1). Most of these questionnaire-based studies used the short form of the International Physical Activity Questionnaire (IPAQ-SF; n = 20) 29,73,76,78,79,82,85,86,112,114,116,130,131,133,138141,146,147 which consists of 6 items assessing time spent in light (i.e., walking), moderate (e.g., carrying light loads, cycling at moderate speed, doubles tennis), and vigorous physical activity (e.g., digging, fast cycling, heavy lifting, aerobics) over the last 7 days 159 . Other questionnaires were used to assess physical activity, such as the Baecke Habitual Physical Activity Questionnaire 160 (BHPAQ; n = 5) 64,89,90,107,113 , Saltin-Grimby Physical Activity Level Scale 161 (SGPALS; n = 5) 80,104,115,125,135 , Godin-Shephard Leisure-Time Exercise Questionnaire 162 (GLTEQ; n = 2) 121,134 , Minnesota Leisure Time Physical Activity Questionnaire 163 (MLTPAQ; n = 1) 136 , Physical Activity Scale for the Elderly 164 (PASE; n = 2) 123,149 , Physical Activity Questionnaire for the Elderly 164 (PAQE; n = 1) 72 , Short Questionnaire to Assess Health Enhancing Physical Activity 165 (SQUASH; n = 1) 142 , the Tegner Assessment Scale 166 (TAS; n = 1) 63 , University of California Los Angeles (UCLA) activity score 167 (n = 1) 84 , Leisure Time Physical Activity Index 168 (LTPAI; n = 1) 67 , Global Physical Activity Questionnaire 169 (GPAQ; n = 2) 77,83 , Freiburger Questionnaire on Physical Activity 170 (FQPA; n = 1) 127 , Jurka Physical Activity Scale 171 (JPAS; n = 1) 81 , Rapid Assessment of Physical Activity questionnaire 172 (RAPAQ; n = 1) 68 , Tecumseh Occupational Activity Questionnaire 173 (TOAQ; n = 1) 136 , and Australian Health Survey-derived questions (AHS; n = 1) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations